Added Value Plastic Waste Recycling Post-pandemic as a Circular Economy in Indonesia - Purwanto, Setiyo; Hikmah Perkasa, Didin (KnE Social Sciences, 2023)
Employee performance is crucial in assessing one’s capacity to compete in the workplace. Good performers will be able to help the business achieve its objectives. This investigation on employee performance takes the shape of a proposed study. This study aims to determine the effect of recruitment, training, and motivation on employee performance. Companies must be able to implement sound strategies and make changes to HR management because business conditions are constantly changing. The fulfillment of HR through recruitment will greatly determine the development of an organization because HR is the most important source of capital. In conducting recruitment, you must look for human resources with competencies that match the company needs. Furthermore, the company must have a clear and measurable training program so that the HR recruited are able to complete all their work properly. Moreover, the role of motivation also determines a person’s work as expected by the company. Many previous studies have stated that there is a link between recruitment, training, and motivation on employee performance. The results are still in the form of a proposal study; for more details whether there is an effect of each variable, it is necessary to analyze research data. Keywords: recruitment, training, motivation, employee performance